Gamification as a didactic alternative for the reflection of the ethics of consumption in the framework of the social sciences (Memorias Sifored - Encuentros Educación UAN, 2021)
Socialize the practical experience of the use of didactic material designed through Gamification for the development of critical thinking around the ethics of consumption within the framework of the didactic class of social sciences.The following questions allowed to articulate the development of this reflection and broaden the perspective of the use of gamification with a tool in school teaching.What is the challenge of thinking about the teaching of some social science topics in terms of gamification?How do the theoretical classes of the social sciences dialogue with didactic alternatives such as gamification?
Keywords: gamification; didactic; ethics; social sciences